PET/CT analysis of 21 patients with breast cancer: physiological distribution of ¹⁸F-choline and diagnostic pitfalls - Ahmad Saad, Fathinul Fikri; Zakaria, Mohd Hazeman; Appanna, Bahunu (SAGE Publications, 2018)
Objectives: ¹⁸F-choline is a useful tracer for detecting tumours with high lipogenesis. Knowledge of its biodistribution pattern is essential to recognise physiological variants. The aim of this study was to describe the physiologic distribution of ¹⁸F-choline and pitfalls in patients with breast cancer. Methods: Twenty-one consecutive patients with breast cancer (10 premenopausal and 11 postmenopausal women; mean age, 52.82 ± 10.71 years) underwent 18F-choline positron emission tomography (PET)/computed tomography (CT) for staging. Whole-body PET/CT was acquired after 40 minutes of 18F-choline uptake. Acquired PET images were measured semiquantitatively. Results: All patients showed pitfalls unrelated to breast cancer. These findings were predominantly caused by physiological glandular uptake in the liver, spleen, pancreas, bowels, axial skeleton (85%-100%), inflammation and benign changes (4.76%), appendicular skeleton (4.76%-19.049%), and site contamination (61.9%). In <1%, a concomitant metastatic neoplasm was found. The breast showed higher physiological uptake in premenopausal compared with postmenopausal woman (¹⁸F-choline maximum standardised uptake values [g/dL] of the right breast = 2.04 ± 0.404 vs 1.59 ± 0.97 and left breast = 2.00 ± 0.56 vs 1.93 ± 1.28, respectively). Conclusion: ¹⁸F-choline uptake was higher in premenopausal women. Physiological ¹⁸F-choline uptake was observed in many sites, representing possible pathologies.